Creating effective visuals for destination marketing videos: Scenery vs people. (January 2023) - Alamäki, Ari; Rhee, Cheul; Suomala, Jyrki; Kaski, Timo; Kauttonen, Janne
By drawing from imagery and consumer choice theories, we examine how visuals of faces and social groups can foster behavioural intention and emotional effects in the case of nature tourism video marketing. We implemented an experimental study by creating three different videos with altering levels of human presence. Data were analysed using linear regression and partial least-squares path analysis methods. Unlike prior research had suggested, video content with fewer direct visuals of human beings was found to be more entertaining. Thus, scenery performed better than people as visuals in our destination marketing case. The visuals of faces and social groups had no effect on consumers' behavioural intention or emotions, even if they did arouse feelings of social presence. Behavioural intention was mainly associated with entertainment value, while social presence had only a minor effect. Gender, nationality and outdoor activity also affected the media effects of videos, showing them to be complex and context-dependent phenomena.